Film for sealant

A packaging film with a resin composition of polypropylene, polyethylene, and silylated polyethylene addresses the challenges of viscous content adhesion and heat seal strength, offering improved easy peeling and barrier properties.

JP2025069256AActive Publication Date: 2025-04-30TOYOBO CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2025012336
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-01-28
Publication Date
2025-04-30
Estimated Expiration
2040-08-21

AI Technical Summary

Technical Problem

Existing packaging bags face challenges with viscous contents adhering to the inner surface, making removal difficult and posing hygiene issues during disposal. Current solutions, such as surfactant-coated or kneaded films, and films with silicone resin or silylated polyolefins, do not adequately address heat seal strength and easy peeling properties.

Method used

A film with a sealing layer composed of a resin composition containing polypropylene resin, polyethylene resin, and silylated polyethylene resin, with specific weight percentages and a silylated polyethylene resin formula, is used. This composition sets the temperature dependence of heat seal strength within a specific range, enhancing easy peeling and heat sealing properties.

Benefits of technology

The solution enables easy removal of viscous contents, maintains sufficient heat sealing properties, and provides excellent slip resistance and blocking resistance, addressing the limitations of prior technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069256000003
    Figure 2025069256000003
  • Figure 2025069256000004
    Figure 2025069256000004
  • Figure 2025069256000005
    Figure 2025069256000005
Patent Text Reader

Abstract

To provide a film and / or a packaging bag which allows the content to be easily taken out from the packaging bag even when the content is viscous, exhibits sufficient heat sealability, and exhibits excellent easy peelability.SOLUTION: A film includes a seal layer composed of a resin composition containing the following (a), (b), and (c), where the contents of (a), (b), and (c) are: 30-70 wt.% of (a), 10-40 wt.% of (b), and 3-30 wt.% of (c), with respect to the total amount of the resin composition. (a) A polypropylene-based resin. (b) A polyethylene-based resin. (c) A silylated polyethylene resin represented by the following structural formula: CH3-(CH2)n-2-CH2-Si(CH3)2O-(-Si(CH3)2-O-)d-Si(CH3)2-CH2-(CH2)n-2-CH3 (where d is an integer of 1 or larger).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sealant film and a laminate using the same. More specifically, the present invention relates to a sealant film having excellent liquid repellency, heat sealability, slippage and anti-blocking properties, and a laminate packaging bag using the same. [Background technology]

[0002] Packaging bags made of plastic film are lightweight, airtight, transparent, strong, and easy to handle, and therefore are widely used to package food, medicines, and other solid, liquid, powder, paste, viscous substances, and mixtures of these substances.

[0003] However, it is well known from experience that when food, medicine, or other substances are removed from a packaging bag, liquid, paste, viscous, or other sticky contents tend to adhere to the inner surface of the bag, making them difficult to remove. In addition, if a packaging bag with contents remaining in it is discarded, this can cause hygiene problems.

[0004] In order to solve these problems, films with a surfactant applied to the surface or films with a surfactant kneaded into them have been proposed (see, for example, Patent Documents 1 and 2). However, they have problems such as making it difficult to remove the contents and reducing the heat seal strength.

[0005] Furthermore, films containing silicone resin or silicone oil and having improved liquid repellency have been proposed (see, for example, Patent Documents 3 and 4), but the liquid repellency is also insufficient.

[0006] Furthermore, films made of silylated polyolefins and having improved liquid repellency have also been proposed (see, for example, Patent Documents 5, 6, 7, etc.). In addition, a film has been proposed in which polyethylene resin is mixed with polypropylene resin to impart easy peelability, but the liquid repellency is insufficient (see, for example, Patent Document 8, etc.). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2000-355362 A [Patent Document 2] JP 2001-48229 A [Patent Document 3] Japanese Patent Application Publication No. 08-337267 [Patent Document 4] Patent No. 3539723 [Patent Document 5] Patent No. 5990131 [Patent Document 6] JP 2014-177541 A [Patent Document 7] JP 2015-024548 A [Patent Document 8] Patent No. 5394096 Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention has been made in consideration of the above technical background, and aims to provide a film and / or a packaging bag that is easy to remove from the packaging bag even if the contents are viscous, exhibits sufficient heat sealing properties, and exhibits excellent easy peel properties. [Means for solving the problem]

[0009] In view of the above circumstances, the present inventors conducted intensive research and found that the above problems can be solved by using a resin composition containing a polypropylene-based resin and a silylated polyolefin, and by setting the temperature dependency of the heat seal strength in a layer made of this resin composition within a specific range, thereby completing the present invention. That is, the present invention is a film for sealant comprising a sealing layer made of a resin composition containing the following (a), (b), and (c), and satisfying the following (1), (2), and (3). (a) Polypropylene resin (b) Polyethylene resin (c) Silylated polyethylene resin (1) The contents of (a), (b) and (c) are 30 to 70% by weight, 10 to 40% by weight and 3 to 30% by weight, respectively, based on the total weight of the resin composition. (2) Silylated polyethylene resin is represented by the following formula. CH3-(CH2) n-2 -CH2-S i (CH3)2O-(-S i (CH3)2-O-) d -S i (CH3)2-CH2-(CH2) n-2 -CH3 (In the formula, d is an integer of 1 or more, and n is an integer of 100 or more.) (3) The polyethylene resin is at least one polyethylene resin selected from the group consisting of high-pressure low-density polyethylene and linear low-density polyethylene.

[0010] Alternatively, the present invention is a film for sealant comprising a sealing layer made of a resin composition containing the following (a), (b), and (c), and satisfying the following (4), (5), and (6). (a) Polypropylene resin (b) Polyethylene resin (c) Silylated polyethylene resin (4) The contents of (a), (b) and (c) are 30 to 85% by weight, 10 to 40% by weight and 3 to 30% by weight, respectively, based on the total weight of the resin composition. (5) Silylated polyethylene resin is represented by the following formula: CH3-(CH2) n-2 -CH2-S i (CH3)2O-(-S i (CH3)2-O-) d -S i (CH3)2-CH2-(CH2) n-2 -CH3 (In the formula, d is an integer of 1 or more, and n is an integer of 100 or more.) (6) The polyethylene resin is an elastomer made of a copolymer of ethylene monomer and an α-olefin.

[0011] In these cases, it is preferable that the resin composition contains particles made of an inorganic oxide or a synthetic resin.

[0012] Furthermore, in these cases, it is preferable that the resin composition contains (d) a fatty acid ester or a fatty acid amide.

[0013] In these cases, it is preferable to satisfy the following (7) and (8): (7) The ratio of silicon atoms (Si) to carbon atoms (C) contained in the sealing layer (S i / C) is 0.001 or more and 0.02 or less. (8) The ratio of silicon atoms (Si) to carbon atoms (C) on the surface of the sealing layer (S i / C) is 0.05 or more and 0.2 or less.

[0014] Furthermore, in these cases, it is preferable to satisfy the following (9). (9) Silicon atoms S contained in the sealing layer i and the abundance ratio of carbon atom C (S i / C) to the silicon atom S on the surface of the sealing layer i and the abundance ratio of carbon atom C (S i / C) ratio is 2 or more.

[0015] Furthermore, in these cases, it is preferable that the blocking value of the surface of the sealing layer is 200 mN / 70 mm or less.

[0016] Furthermore, a laminate comprising the above sealant film and a base film is preferred. Effect of the Invention

[0017] The present invention provides a packaging bag that allows easy removal of contents even when the contents are pasty, viscous, or other viscous materials, and provides a sealant film and a laminate thereof that have good heat sealing properties as well as excellent slip properties and blocking resistance. [Brief description of the drawings]

[0018] [Figure 1] Average Si concentration and surface Si concentration of the films described in Comparative Examples 1 and 4, Examples 2 to 4, and 13 [Diagram 2] Schematic diagram of the procedure for evaluating liquid repellency [Diagram 3] EDX mapping measurement of film surface [Figure 4] TEM observation of film cross section [Diagram 5] Photo of the area around the die nozzle of a resin extrusion machine DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] (Sealing layer) In the present invention, the resin composition constituting the seal layer must contain (a) a polypropylene-based resin, (b) a polyethylene-based resin, and (c) a silylated polyolefin resin.

[0020] (Polypropylene resin) The polypropylene-based resin used in the present invention is a homopolymer of a propylene monomer, a random copolymer and / or a block copolymer of a propylene monomer and an α-olefin, or a mixture thereof. Examples of the α-olefin include ethylene, butene-1, pentene-1, hexene-1, 3-methylbutene-1, 4-methylpentene-1, octene-1, and decene-1.

[0021] The polypropylene resin used is preferably a homopolypropylene or a polypropylene random copolymer, and more preferably a polypropylene-α-olefin random copolymer, which is a random copolymer of 85% by weight or more of propylene and 15% by weight or less of an α-olefin. As the α-olefin monomer for obtaining such a polypropylene random copolymer, ethylene, butene-1, pentene-1, 4-methylpentene-1, hexene-1, octene-1, etc. can be used, but from the viewpoint of productivity, it is particularly preferable to use ethylene and butene-1. In addition, the α-olefin used for copolymerization may be at least one type, and if necessary, two or more types can be mixed and used.

[0022] The peak melting point of the polypropylene resin is preferably 130° C. or higher. The melting point is measured by the method described in the Examples below. If the melting point peak temperature of the polypropylene resin is 130°C or higher, the shape of the package is less likely to collapse, the film can be conveyed more smoothly in high-speed packaging processing, and the obtained bag product is less likely to wrinkle. In addition, retort processing or semi-retort processing can be performed.

[0023] The lower limit of the density of the polypropylene resin is preferably 880 kg / cm 3 and more preferably 885 kg / cm 3 880kg / cm 3 The upper limit of the density of the polypropylene resin added to the sealing layer is preferably 920 kg / cm. 3 and more preferably 900 kg / cm 3 920kg / cm 3 It is preferable that the content be not more than 100% since both heat resistance and heat sealability can be achieved.

[0024] The lower limit of the melt flow rate (MFR) of the polypropylene resin is preferably 2.0 g / 10 min, more preferably 2.5 g / 10 min, and further preferably 2.7 g / 10 min. If it is 2.0 g / 10 min or more, the polypropylene resin and the polyethylene resin tend to be finely dispersed without layer separation, and the peel strength between the seal layers after heat sealing is not excessively reduced. The upper limit of the melt flow rate of the polypropylene resin is preferably 10.0 g / 10 min, more preferably 8.0 g / 10 min, and even more preferably 7.0 g / 10 min. If it is 10.0 g / 10 min or less, the polypropylene and polyethylene resin are not compatible with each other and tend to be finely dispersed, and the peel strength between the seal layers after heat sealing is not excessively reduced.

[0025] (Polyethylene resin) The polyethylene resin used in the present invention is a copolymer of an ethylene monomer and an α-olefin. Examples of the α-olefin include propylene, butene-1, hexene-1, 4-methylpentene-1, octene-1, decene-1, 3-methylbutene-1, 4-methylpentene-1, and octene-1. The copolymer of ethylene monomer and α-olefin referred to here is generally called high-pressure low-density polyethylene, linear low-density polyethylene, or polyethylene-based elastomer. Elastomer means an olefin-based thermoplastic copolymer that exhibits rubber-like elasticity around room temperature. The melting points of high-pressure low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and polyethylene-based elastomer are preferably in the range of 50 to 140°C.

[0026] In the present invention, the density range of the raw polyethylene resin used in the blending is 850 to 970 kg / m 3 is preferable, and 860 to 965 kg / m 3 More preferably, 865 to 960 kg / m 3 More preferably, the density is 850 kg / m 3 The polyethylene resin does not have too much peel strength after heat sealing between the sealing layers. Density is 970kg / m 3 The following polyethylene resins also do not show excessive decrease in peel strength after heat sealing between the seal layers, and are easy to polymerize.

[0027] The lower limit of the melt flow rate (MFR) of the polyethylene resin is preferably 0.6 g / 10 min, more preferably 1.0 g / 10 min, and further preferably 1.5 g / 10 min. If it is 0.6 g / 10 min or more, fine dispersion of polypropylene and polyethylene resin is easily obtained, and the peel strength after heat sealing between the seal layers is not excessively decreased. The upper limit of the melt flow rate of the polyethylene resin is preferably 5.0 g / 10 min, more preferably 4.0 g / 10 min, further preferably 3.5 g / 10 min, and particularly preferably 3.0 g / 10 min or less. If it is 5.0 g / 10 min or less, fine dispersion of polypropylene and polyethylene resin is easily obtained, and the peel strength after heat sealing between the seal layers is easily reduced.

[0028] When the polypropylene-based resin and the polyethylene-based resin are blended and melted, it is possible to create a finely dispersed state, which can reduce the strength at the time of peeling after heat sealing between the sealing layers or between the sealing layer and the periphery of the opening of another container component.

[0029] After heat sealing between seal layers or between a seal layer and the periphery of the opening of another container component, the peel strength tends to decrease in the following order: ethylene copolymer (polyethylene elastomer), LLDPE, LDPE. The reason for this is presumably that while ethylene copolymers are incompatible with polypropylene resins only in the ethylene portion, LLDPE has side chains that allow for fine dispersion, and LDPE has long side chains that allow for strong fine dispersion.

[0030] Specifically, density is 885kg / m 3 , MFR (230°C, 2.16 kg) 2.2 g / 10 min ethylene-butene copolymer elastomer (Tafmer A1085S, Mitsui Chemicals, Inc.), density 869 kg / m 3 An example of such a polymerizable composition is an ethylene-propylene copolymer elastomer having a MFR (230° C., 2.16 kg) of 1.8 g / 10 min (Tafmer P0480, manufactured by Mitsui Chemicals, Inc.).

[0031] (Silylated polyolefin resin) The silylated polyolefin resin used in the present invention has S in the molecule. i It is obtained by reacting a silicon-containing compound having two or more H groups with a vinyl group-containing compound which is a polymer of at least one olefin selected from the group consisting of ethylene, propylene, 1-butene, 1-pentene, and 1-hexene and contains a vinyl group at the terminal.

[0032] S i Examples of silicon-containing compounds having two or more H groups include methylhydrogenpolysiloxanes represented by formula (1) and compounds in which some or all of the methyl groups in formula (1) have been substituted with ethyl groups, propyl groups, phenyl groups, trifluoropropyl groups, etc. Formula (1) (CH3)3S i O-(-S i H(CH3)-O-) a -S i (CH3)3 (In formula (1), a is an integer of 2 or more, and the upper limit is preferably 1000, more preferably 300, and even more preferably 50.)

[0033] S i Other examples of silicon-containing compounds having two or more H groups include dimethylsiloxane-methylhydrogensiloxane copolymers represented by formula (2) and compounds in which some or all of the methyl groups in formula (2) have been replaced with ethyl groups, propyl groups, phenyl groups, trifluoropropyl groups, etc. Formula (2) (CH3)3S i O-(-S i (CH3)2-O-) b -(-S i H(CH3)-O-) c -S i (CH3)3 (In formula (2), b is an integer of 1 or more, c is an integer of 2 or more, and the upper limit of the total of b and c is preferably 1000, more preferably 300, and even more preferably 50.) In formula (2), -S i (CH3)2-O-units and -S i The order in which the H(CH3)-O- units are arranged is not particularly limited, and may be block-like, disordered, or statistically random.

[0034] S i Further examples of silicon-containing compounds having two or more H groups include methylhydrogenpolysiloxanes represented by formula (3) and compounds in which some or all of the methyl groups in formula (3) have been substituted with ethyl groups, propyl groups, phenyl groups, trifluoropropyl groups, etc. Formula (3) HS i (CH3)2O-(-S i (CH3)2-O-) d -S i (CH3)2H (In formula (3), d is an integer of 1 or more, and the upper limit is preferably 1000, more preferably 300, and even more preferably 50.)

[0035] More specifically, examples of such compounds include compounds whose structures corresponding to their number average molecular weights are shown below, but are not limited to these. HS i (CH3)2O-(-S i (CH3)2-O-)5-S i (CH3)2H HS i (CH3)2O-(-S i (CH3)2-O-)8-S i (CH3)2H HS i (CH3)2O-(-S i (CH3)2-O-) 18 -S i (CH3)2H HS i (CH3)2O-(-S i (CH3)2-O-)80 -S i (CH3)2H HS i (CH3)2O-(-S i (CH3)2-O-) 230 -S i (CH3)2H

[0036] (vinyl group-containing compound) The vinyl group-containing compound used in the present invention is obtained by copolymerizing or polymerizing at least one olefin selected from the group consisting of ethylene, propylene, 1-butene, 1-pentene, and 1-hexene.

[0037] The vinyl group-containing compound is preferably an ethylene-α-olefin copolymer containing 81 to 100 mol % of structural units derived from ethylene and 0 to 19 mol % of structural units derived from an α-olefin having 3 to 20 carbon atoms. More preferably, it is an ethylene-α-olefin copolymer containing 90 to 100 mol % of structural units derived from ethylene and 0 to 10 mol % of structural units derived from an α-olefin having 3 to 20 carbon atoms. In particular, it is preferable that the structural units derived from ethylene are 100 mol %.

[0038] Moreover, the vinyl group-containing compound preferably has a molecular weight distribution (ratio of weight average molecular weight to number average molecular weight, Mw / Mn) measured by gel permeation chromatography (GPC) in the range of 1.1 to 3.0.

[0039] The vinyl group-containing compound desirably has a number average molecular weight (Mn) in the range of 100 or more and 500,000 or less, more preferably 500 or more and 300,000 or less, and even more preferably 1,500 or more and 100,000 or less.

[0040] The vinyl group-containing compound preferably has a melting point of 70° C. or more and 130° C. or less. The vinyl group-containing compound in the present invention preferably has a number average molecular weight, as determined by GPC, of ​​100 to 500,000, more preferably 500 to 300,000, and even more preferably 1,500 to 100,000.

[0041] The vinyl group of the vinyl group-containing compound is preferably present at a terminal of the main chain, and more preferably, the vinyl group is present only at the terminal of the main chain.

[0042] In addition, when the vinyl group-containing compound contains a vinyl group only at the terminal of the main chain, 1 The percentage of terminal unsaturation calculated by H-NMR is 80 mol % or more and 99.5 mol % or less, more preferably 90 mol % or more and 99 mol % or less.

[0043] (Method of producing silylated polyolefin resin) The silylated polyolefin resin used in the present invention is a silylated polyolefin resin or a derivative thereof, or a mixture thereof, obtained by reacting the above-mentioned vinyl group-containing compound with a silicon-containing compound in the presence of a transition metal catalyst according to the method described in JP 2014-223752 A.

[0044] Specific examples of silylated polyolefin resins include those having structures represented by formulas (4) to (6), but the combinations of silicon-containing compounds and vinyl group-containing compounds are not limited to these examples.

[0045] Formula (4) (CH3)3S i O-(-S i [CH2-(CH2) n-2 -CH3](CH3)-O-) a -Si(CH3)3 (In formula (4), a is an integer of 2 or more, and the upper limit is preferably 1000, more preferably 300, and even more preferably 50.)

[0046] Formula (5) (CH3)3S i O-(-S i (CH3)2-O-) b -(-S i [CH2-(CH2) n-2 -CH3](CH3)-O-) c -S i (CH3)3 (In formula (5), b is an integer of 1 or more, c is an integer of 2 or more, and the upper limit of the total of b and c is preferably 1000, more preferably 300, and even more preferably 50.)

[0047] Formula (6) CH3-(CH2) n-2 -CH2-S i (CH3)2O-(-S i (CH3)2-O-) d -S i (CH3)2-CH2-(CH2) n-2 -CH3 (In formula (6), d is an integer of 1 or more, and the upper limit is preferably 1000, further preferably 300, further preferably 50, and particularly preferably 25.)

[0048] The silylated polyolefin resin used in the present invention preferably contains 80% by weight or more, and particularly preferably 90% by weight or more, of a block copolymer in which both ends of polydimethylsiloxane are polyethylene, as shown in formula (6). In formula (6), d is preferably an integer of 3 or more, and more preferably 10 or more. In the formulas (4) to (6), n is preferably an integer of 100 or more, and more preferably 150 or more.

[0049] In order to obtain the properties of the film of the present invention and to produce the film of the present invention, the silylated polyolefin resin used in the present invention preferably satisfies the following i) and ii), more preferably satisfies the following i) to iii), and even more preferably satisfies the following i) to iv). i) Density is 900-1000kg / m 3 The range is. ii) The melting point is in the range of 100 to 140°C. iii) The number average molecular weight is in the range of 1,000 to 20,000. iv) The copolymerization rate of silicone is in the range of 1 to 50% by weight. The chemical formula and molecular weight of the silylated polyolefin resin are identified by the method described in the Examples.

[0050] (Resin composition) When the polyethylene is LDPE or LLDPE, the contents of (a) polypropylene-based resin, (b) polyethylene-based resin, and (c) silylated polyolefin resin in the resin composition constituting the sealing layer must be 30 to 70% by weight, 10 to 40% by weight, and 3 to 30% by weight, respectively, relative to the total resin composition. (a) The content of the polypropylene resin in the resin composition is more preferably 35% by weight or more, further preferably 40% by weight or more, and particularly preferably 55% by weight or more. (a) When the polypropylene resin is contained in an amount of 30% by weight or more, the firmness is maintained. The content of the polypropylene resin in the resin composition is more preferably 65% ​​by weight or less, and further preferably 60% by weight or less.(a) When the content of the polypropylene resin is 70% by weight or less, easy peel property is observed. (b) The content of the polyethylene resin in the resin composition is more preferably 12% by weight or more, further preferably 15% by weight or more, and particularly preferably 20% by weight or more. When the polyethylene resin is contained in an amount of 10% by weight or more, the peel strength between the seal layers after heat sealing is likely to decrease. The content of the (b) polyethylene resin in the resin composition is more preferably 35% by weight or less, more preferably 30% by weight or less, and even more preferably 20% by weight or less. When the content of the (b) polyethylene resin is about 40% by weight, the heat resistance is unlikely to decrease. (c) The content of the silylated polyolefin resin in the resin composition is more preferably 5% by weight or more, further preferably 7% by weight or more, and particularly preferably 12% by weight or more. When the silylated polyolefin resin is contained in an amount of 3% by weight or more, sufficient liquid repellency is obtained, and the liquid repellency against edible oil is particularly excellent. The content of the (c) silylated polyolefin resin in the resin composition is more preferably 28% by weight or less, even more preferably 25% by weight or less, even more preferably 20% by weight or less, and even more preferably 15% by weight or less. When the content of the (c) silylated polyolefin resin is about 30% by weight, the liquid repellency effect is hardly improved any more. The lower the content of the (c) silylated polyolefin resin, the less segregation occurs on the surface of the seal layer.

[0051] When the polyethylene-based resin is an elastomer, the contents of (a) the polypropylene-based resin, (b) the polyethylene-based resin, and (c) the silylated polyolefin resin in the resin composition constituting the sealing layer must be 30 to 85% by weight, 10 to 40% by weight, and 3 to 30% by weight, respectively, relative to the total weight of the resin composition. (a) The content of the polypropylene resin in the resin composition is more preferably 35% by weight or more, further preferably 40% by weight or more, and particularly preferably 55% by weight or more. (a) When the polypropylene resin is contained in an amount of 30% by weight or more, the firmness is maintained. The content of the polypropylene resin in the resin composition is more preferably 80% by weight or less, and further preferably 75% by weight or less. (a) When the polypropylene resin is contained in an amount of 70% by weight or less, easy peel property is maintained. (b) The content of the polyethylene resin in the resin composition is more preferably 12% by weight or more, further preferably 15% by weight or more, and particularly preferably 20% by weight or more. When the polyethylene resin is contained in an amount of 10% by weight or more, the peel strength between the seal layers after heat sealing is likely to decrease. The content of (b) polyethylene resin in the resin composition is more preferably 35% by weight or less, even more preferably 30% by weight or less, and even more preferably 20% by weight or less. When the content of (b) polyethylene resin is about 40% by weight, heat resistance is unlikely to decrease. The content of (c) silylated polyolefin resin in the resin composition is more preferably 5% by weight or more, even more preferably 7% by weight or more, and particularly preferably 12% by weight or more. When the content of silylated polyolefin resin is 3% by weight or more, sufficient liquid repellency is obtained, and liquid repellency against edible oil is particularly excellent. The content of the (c) silylated polyolefin resin in the resin composition is more preferably 25% by weight or less, even more preferably 20% by weight or less, and even more preferably 15% by weight or less. When the content of the (c) silylated polyolefin resin is about 30% by weight, the liquid repellency effect is hardly improved any more. The lower the content of the (c) silylated polyolefin resin, the less segregation to the surface of the seal layer. The contents of (a) polypropylene resin, (b) polyethylene resin, and (c) silylated polyolefin are determined by the method described in the Examples.

[0052] (particle) The resin composition constituting the sealing layer preferably contains particles, and the particles are preferably made of inorganic oxide or synthetic resin. By containing particles, the arithmetic mean roughness Ra of the surface of the sealing layer is easily set to 0.03 μm or more and 0.3 μm or less. As a result, the dynamic friction coefficient between the surfaces of the sealing layer of the film or between the sealing layer and the surface of the opposite side, and the blocking strength of the lubricity between the surfaces of the sealing layer of the film are easily significantly reduced. The reason for this is thought to be that (c) the silylated polyolefin resin is unevenly distributed on the surface of the sealing layer, and by imparting specific irregularities to the film surface, which has reduced crystallinity and hardness, the effect of reducing the deterioration is reduced, and the dynamic friction coefficient and blocking strength are greatly reduced. The weight average particle size of the particles made of inorganic oxide or synthetic resin is preferably 2 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more, and is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. The weight average particle diameter is measured by the method described in the Examples. Examples of the particles made of synthetic resin include crosslinked acrylic particles, polymethacrylic acid particles, silicone resin particles, and polyethylene particles. Examples of particles made of inorganic oxides include particles made of silicon oxide, particles made of calcium carbonate, zeolite, and particles made of diatomaceous earth. Among the particles made of silicon oxide, it is preferable to use silica particles or synthetic silica particles, but diatomaceous earth may also be used in combination. The content of the particles made of inorganic oxide or synthetic resin in the resin composition is preferably 0.1% by weight or more, more preferably 0.3% by weight or more, and even more preferably 0.4% by weight or more. Also, it is preferably 3.0% by weight or less, more preferably 2.5% by weight or less, and even more preferably 2.0% by weight or less. When the content of the particles made of inorganic oxide or synthetic resin is 3.0% by weight or less, the projections on the surface do not become too large, and the liquid repellency is not easily reduced.

[0053] (Organic lubricants) The resin composition constituting the seal layer preferably contains an organic lubricant, and the organic lubricant is preferably a fatty acid amide. By containing the organic lubricant, the arithmetic mean roughness Ra of the surface of the seal layer is set to 0.03 μm or more and 0.3 μm or less, and the blocking resistance and slippage of the seal layer are easily improved by the synergistic effect of the organic lubricant and the arithmetic mean roughness Ra of the surface of the seal layer being set to 0.03 μm or more and 0.3 μm or less. Examples of fatty acid amides include oleic acid amide, erucic acid amide, behenic acid amide, ethylene bis oleic acid amide, hexamethylene bis oleic acid amide, etc. These may be used alone, but it is preferable to use two or more of them in combination, since this makes it possible to maintain lubricity and anti-blocking effects even under harsh environments. On the other hand, fatty acid esters are widely known as emulsifiers and are also known to have the effect of imparting hydrophilicity to the film surface as anti-fogging agents, but in the present invention, they are not preferred because they not only reduce water repellency but also impair oil repellency. In addition, many fatty acid esters have low melting points, and there is concern about stickiness and poor appearance due to bleed-out. In consideration of these points, fatty acid amides are preferred. It is preferable to add an organic lubricant with a melting point of 25°C or higher. The content of (d) fatty acid amide and fatty acid ester in the resin composition is preferably 0.01 to 0.5 wt%, more preferably 0.05 to 0.4 wt%, and particularly preferably 0.1 to 0.3 wt%. If the fatty acid amide is 0.5 wt% or less, the seal strength is unlikely to decrease.

[0054] (others) The resin composition may contain additives such as antioxidants, heat stabilizers, weather stabilizers, and crystal nucleating agents, as well as ethylene-vinyl acetate copolymers and ethylene-acrylate copolymers, as necessary, within the scope of not impairing the performance of the sealant film of the present invention.

[0055] (Film forming method) As a method for producing the sealant film of the present invention, it is preferable to adopt, for example, a step of melt-kneading a polypropylene-based resin composition containing a polyethylene-based resin, a step of melt-extruding the melt-kneaded resin composition to form a molten resin composition sheet, and a step of cooling and solidifying the molten resin composition sheet. The sealant film of the present invention may be a single layer, but is preferably a laminate. In the case of a laminate, a layer containing a polyethylene resin and a silylated polyolefin and having an arithmetic mean roughness of 0.03 μm or more and 0.3 μm or less on at least one surface side can be provided with another layer made of a thermoplastic resin composition, preferably a polyolefin resin composition. In the case of a single layer, the thickness of the film is preferably 3 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and particularly preferably 20 μm or more. Also, it is preferably 200 μm or less, more preferably 150 μm or less, and particularly preferably 100 μm or less. If it is less than 3 μm, the effect of the silica particles decreases, and the effect of anti-slip and anti-locking properties is not easily obtained. The details are explained below. The longitudinal direction means the direction in which the unstretched sheet runs, and the width direction means the direction perpendicular thereto.

[0056] (Raw material mixing process) When mixing a silylated polyolefin resin with a polyethylene-based resin, or particles such as silica particles with a polypropylene-based resin, any method that can mix them uniformly may be used. In the case of using a master batch, examples of the method include mixing using a ribbon blender, a Henschel mixer, a tumbler mixer, etc.

[0057] (Melting and kneading process) First, the film raw material, polypropylene resin, etc., is dried or hot air dried so that the moisture content is less than 1000 ppm. Next, each raw material is weighed, mixed, and fed to an extruder and melt-kneaded. The lower limit of the melt mixing temperature of the polyethylene resin composition is preferably 200°C, more preferably 210°C, and even more preferably 220°C. If the temperature is lower than the above, discharge may become unstable. The upper limit of the resin melting temperature is preferably 260°C. If the temperature exceeds the above, decomposition of the resin proceeds, and the amount of crosslinked organic matter, so-called gel, and other foreign matter generated as a result of recombination increases. When the polyethylene resin composition contains the above-mentioned antioxidant, melt extrusion at a higher temperature becomes possible, but it is preferable to keep the temperature at 270° C. or lower.

[0058] (Filtration) In the melt-kneading process, high-precision filtration can be performed to remove foreign matter contained in the molten polyethylene resin composition. The filter material used for high-precision filtration of molten resin is not particularly limited, but in the case of a filter material made of stainless steel sintered body, it is excellent in removing foreign matter such as gel, as well as agglomerates mainly composed of Al, Si, Ti, Sb, Cu, and Ge derived from additives such as catalysts, and is suitable. In addition, the filtration accuracy is preferably 200 μm or less.

[0059] (Filter boost) The amount of pressure increase during melt kneading of the polyethylene resin composition is preferably small.

[0060] (Melt extrusion process) Next, the molten polypropylene resin composition sheet is melt-extruded, for example, through a T-shaped die, cast onto a cooling roll, and cooled and solidified to obtain an unstretched sheet. As a specific method for this, casting onto a cooling roll is preferred. The silylated polyolefin used in the present invention is a copolymer with polyethylene, so no bleed-out is observed even after melt-kneading and extrusion processes, and the accumulation of foreign matter and gunk that occurs when silicone resin is added is extremely unlikely to occur. Examples of methods include melt-extruding a melt-kneaded polypropylene resin composition sheet and forming it into a film by the T-die method or inflation method, and the like. The T-die method is particularly preferable because it allows the melting temperature of the resin to be increased.

[0061] (Lip stains (bleed out)) When silylated polyolefin, silica particles, and a polypropylene resin are melt-extruded through a T-die, it is preferable that the lip opening of the T-die is less dirty. The lip dirt was measured by the method described in the Examples.

[0062] (Cooling solidification process) For example, it is preferable to cast a molten sheet of the polyethylene resin composition melt-extruded from a T-shaped die onto a cooling roll and then cool it. The lower limit of the cooling roll temperature is preferably 10°C. If it is less than the above, not only may the crystallization suppression effect become saturated, but also problems such as condensation may occur, which is not preferable. The upper limit of the cooling roll temperature is preferably 70°C or less. If it exceeds the above, crystallization will proceed and transparency will deteriorate, which is not preferable. Furthermore, when the cooling roll temperature is in the above range, it is preferable to reduce the humidity of the environment near the cooling roll to prevent condensation. During casting, the surface of the chill roll is in contact with a high-temperature resin, so the temperature of the surface of the chill roll rises. Usually, the chill roll is cooled by running cooling water through piping inside, but it is necessary to reduce the temperature difference in the width direction of the chill roll surface by ensuring a sufficient amount of cooling water, devising an appropriate arrangement of the piping, and performing maintenance to prevent sludge from adhering to the piping. In this case, the thickness of the unstretched sheet is preferably in the range of 3 to 200 μm.

[0063] (Multi-layer structure) The sealant film of the present invention preferably has a multi-layer structure. In the case of a multi-layer structure, in addition to having a layer containing a polyolefin resin and a silylated polyolefin and having an arithmetic mean roughness of a surface layer of 0.03 μm or more and 0.3 μm or less on at least one side, one or more other layers made of a thermoplastic resin composition, preferably a polyolefin resin composition, may be provided. By using a multi-layer structure in which the silylated polyolefin resin is contained only in the surface layer, the amount of the silylated polyolefin resin used can be reduced, and its precipitation can also be reduced. Furthermore, other properties of the film can be improved and new functions can be imparted. As a specific method for forming a multi-layer structure in this way, a general multi-layering device (such as a multi-layer feed block, a static mixer, or a multi-layer multi-manifold) can be used. For example, a method can be used in which thermoplastic resins discharged from different flow paths using two or more extruders are laminated in multiple layers using a feed block, a static mixer, a multi-manifold die, etc. It is also possible to use only one extruder and introduce the above-mentioned multi-layering device into the melt line from the extruder to the T-die.

[0064] In the case of a two-layer structure, it is preferable that at least one layer contains a polyolefin resin and a silylated polyolefin resin and has a surface layer with an arithmetic mean roughness of 0.03 μm or more and 0.3 μm or less, and is designated as a sealing layer (layer A), and the other layer made of a thermoplastic resin composition, preferably a polyolefin resin composition, is designated as a laminate layer (layer C).

[0065] In the case of a three-layer structure, at least one layer contains a polyolefin resin and a silylated polyolefin resin, and the surface layer has an arithmetic mean roughness of 0.03 μm or more and 0.3 μm or less, and is a seal layer (layer A), and other layers made of a thermoplastic resin composition, preferably a polyolefin resin composition, are an intermediate layer (layer B) and a laminate layer (layer C), respectively, in that order. The outermost layers are layer A and layer C, respectively.

[0066] The polyolefin resin used for the intermediate layer (B layer) and laminate layer (C layer) is preferably a polyethylene resin or a polypropylene resin.

[0067] (Polyethylene resin) The polyethylene resin used in the intermediate layer (B layer) and laminate layer (C layer) is any one of a homopolymer of an ethylene monomer, a copolymer of an ethylene monomer and an α-olefin, a copolymer of an ethylene monomer and another monomer, and a mixture thereof. Examples of the α-olefin include propylene, butene-1, hexene-1, 4-methylpentene-1, octene-1, decene-1, 3-methylbutene-1, 4-methylpentene-1, and octene-1. Examples of the other monomers include vinyl acetate, (meth)acrylic acid, and (meth)acrylic acid esters. The polyethylene resin may be a crystalline, low crystalline or non-crystalline random or block copolymer, or a mixture thereof. Copolymers of ethylene monomer and α-olefins are generally also called high-pressure low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, and high-density polyethylene. The use of these polyethylene resins provides excellent heat seal strength, hot tack properties, impurity sealability, and impact resistance, but it is preferable that they contain a small amount of or no copolymer of ethylene monomer with other monomers. In this case, the polyethylene resins used in the intermediate layer (B layer) and the laminate layer (C layer) may be the same or different.

[0068] In this case, it is preferable that the average density of the polyethylene resin in each layer of the film is such that: sealant layer (layer A) ≦ intermediate layer (layer B) ≦ laminate layer (layer C). The organic lubricant contained in the film does not easily migrate to layers with high density, so it is effective in maintaining the slipperiness of the sealant layer after lamination. In this case, the lower limit of the density of the intermediate layer (B layer) is preferably 880 kg / m 3 and more preferably 890 kg / m 3 and more preferably 900 kg / m 3 It is. If it is less than the above, the strength may be weak and processing may be difficult. The upper limit of the density of the intermediate layer (B layer) is preferably 940 kg / m 3 and more preferably 930 kg / m 3 and more preferably 920 kg / m 3 It is.

[0069] (Polypropylene resin) The polypropylene-based resin used in the intermediate layer (B layer) and laminate layer (C layer) is a homopolymer of a propylene monomer, a random copolymer and / or a block copolymer of a propylene monomer and an α-olefin, or a mixture thereof. Examples of the α-olefin include ethylene, butene-1, pentene-1, hexene-1, 3-methylbutene-1, 4-methylpentene-1, octene-1, and decene-1.

[0070] The organic lubricant may be used in the intermediate layer (layer B) of the film of the present invention, and the lower limit of the organic lubricant is preferably 200 ppm, more preferably 400 ppm. If the amount is less than the above, the slipping property may deteriorate. The upper limit of the erucamide concentration in the intermediate layer is preferably 2000 ppm, more preferably 1500 ppm. If it exceeds the upper limit, it becomes too slippery and may cause winding slippage.

[0071] The intermediate layer (layer B) of the film of the present invention may contain 10 to 30% by mass of recycled resin. In the present invention, it is preferable to subject the laminate layer (layer C) surface of the polyethylene sealant film exemplified above to actinic ray treatment such as corona treatment, which improves the laminate strength.

[0072] (Film characteristics) The characteristics of the sealant film of the present invention will now be described in detail. (Ratio of silicon atoms (Si) to carbon atoms (C) in the seal layer (average Si concentration)) The ratio (Si / C) of silicon atom Si to carbon atom C in the seal layer of the sealant film of the present invention is preferably 0.001 or more. If it is 0.001 or more, the liquid repellency against viscous contents such as edible oil, pork cutlet sauce, soy sauce, etc. is improved. It is more preferably 0.005 or more, even more preferably 0.007 or more, and particularly preferably 0.01 or more. The ratio (Si / C) of silicon atom Si to carbon atom C in the seal layer of the sealant film of the present invention is preferably 0.02 or less. When it is 0.02 or less, the peel strength is unlikely to decrease. It is more preferably 0.018 or less, and further preferably 0.016 or less. The measurement is carried out according to the method described in the Examples.

[0073] (Silicon atoms on the surface of the sealing layer S i and the abundance ratio of carbon atom C (S i / C)(Surface S i concentration)) The ratio of silicon atoms Si to carbon atoms C (S i / C) is preferably 0.05 or more. When it is 0.05 or more, the liquid repellency against contents exhibiting viscous properties such as edible oil, pork cutlet sauce, soy sauce, etc. is improved, and the effect of improving the liquid repellency against edible oil is particularly large. It is more preferably 0.07 or more, even more preferably 0.1 or more, preferably 0.13 or more, and particularly preferably 0.15 or more. Silicon atoms S on the surface of the sealing layer of the sealant film of the present invention i and the abundance ratio of carbon atom C (S i / C) is preferably 0.3 or less. If it is 0.3 or less, the heat seal strength is likely to decrease. It is more preferably 0.2 or less. The measurement is carried out according to the method described in the Examples.

[0074] (Ratio of surface Si concentration to average Si concentration) Silicon atoms S contained in the sealing layer of the sealant film of the present invention i and the abundance ratio of carbon atom C (S i / C) to the silicon atom S on the surface of the sealing layer i and the abundance ratio of carbon atom C (S i / C) is preferably 2 or greater, more preferably 3 or greater, even more preferably 5 or greater, even more preferably 6 or greater, particularly preferably 8 or greater, and most preferably 10 or greater. The measurement is carried out according to the method described in the Examples. (Arithmetic mean roughness Ra) The arithmetic mean roughness Ra of the surface of the sealing layer of the sealant film of the present invention is preferably 0.03 μm or more. If it is 0.03 μm or more, the dynamic friction coefficient between the layers or between the layer and the film surface opposite the layer is reduced, and the dynamic friction coefficient between the surfaces of the sealing layers of the film or between the sealing layer and the surface of the opposite surface is easily reduced. The blocking strength of the lubricity between the surfaces of the sealing layers of the film is also easily reduced. As a result, the handling of the film is improved. The arithmetic mean roughness of the surface of the sealing layer is more preferably 0.05 μm or more, and even more preferably 0.07 μm or more. The arithmetic mean roughness Ra of the surface of the seal layer of the sealant film of the present invention is preferably 0.3 μm or less. If it is 0.3 μm or less, the dynamic friction coefficient between the layers or between the layer and the film surface opposite the layer is not too small, so that the film is less likely to slip when wound, and the handling of the film is improved. It is more preferably 0.25 or less. The measurement is carried out according to the method described in the Examples.

[0075] (Maximum protrusion height Rz) The maximum projection height Rz of the surface of the sealing layer of the sealant film of the present invention is preferably 1 μm or more. If it is 1 μm or more, the contact area between the layers or between the layer and the film surface opposite the layer is reduced, the blocking prevention effect is greatly improved, and the handling of the film is improved. The maximum projection height Rz of the surface of the sealing layer is more preferably 1 μm or more, and even more preferably 3 μm or more. The maximum projection height Rz of the surface of the seal layer of the sealant film of the present invention is preferably 30 μm or less. If it is 30 μm or less, the volume of the gap between the layers or between the layer and the film surface on the opposite side of the layer is not too large, so that the film is less likely to slip when wound, and the handling of the film is improved. It is more preferably 25 μm or less. The measurement is carried out according to the method described in the Examples.

[0076] (Young's modulus / longitudinal direction) The lower limit of the Young's modulus (longitudinal direction) of the sealant film of the present invention is preferably 100 MPa, more preferably 150 MPa, further preferably 200 MPa, and particularly preferably 250 MPa. If it is 100 MPa or more, the film is not too weak and is easy to process. The upper limit of the Young's modulus (longitudinal direction) of the sealant film of the present invention is preferably 600 MPa, more preferably 500 MPa, and further preferably 400 MPa.

[0077] (Young's modulus / width direction) The lower limit of the Young's modulus (width direction) of the sealant film of the present invention is preferably 100 MPa, more preferably 150 MPa, further preferably 200 MPa, and particularly preferably 250 MPa. If it is 100 MPa or more, the film is not too weak and is easy to process. The upper limit of the Young's modulus (width direction) of the sealant film of the present invention is preferably 600 MPa, more preferably 500 MPa, and further preferably 400 MPa.

[0078] (Hayes) The upper limit of the haze of the sealant film of the present invention is preferably 15%, more preferably 10%, and further preferably 6%. If it is 15% or less, the contents can be easily visually recognized. The lower limit of the haze of the sealant film of the present invention is preferably 0%, but even 2% is practically satisfactory. The measurement is carried out according to the method described in the Examples.

[0079] (liquid repellency) The residual amount of sticky contents such as edible oil, pork cutlet sauce, and soy sauce, which is an index for evaluating the liquid repellency of the sealant film of the present invention, is 0.08 mg / 28 cm for at least two of these. 2 It is preferable that the concentration is less than 0.8 mg / 28 cm for the three types. 2 It is more preferable that: The measurement is carried out according to the method described in the Examples.

[0080] (Silylated polyolefin resin state) In the seal layer of the sealant film of the present invention, the silylated polyolefin resin is preferably segregated on the surface, but it is preferable that the silylated polyolefin resin is not deposited in a separated state on the surface of the seal layer. In this case, it is preferable that the silylated polyolefin resin is finely dispersed in the sealing layer of the sealant film of the present invention, and that the sealing layer exhibits a microphase separation structure. The state of the silylated polyolefin resin or silicone resin on the surface of the sealing layer can be observed using a scanning electron microscope, and qualitative analysis of the Si and C elements can also be performed using energy dispersive X-rays. The cross section of the sealing layer can also be observed using a transmission electron microscope. The measurement is carried out by the method described in the Examples.

[0081] (Kinematic friction coefficient) The upper limit of the dynamic friction coefficient between the seal layers of the sealant film of the present invention is preferably 1.5, more preferably 1.0, even more preferably 0.7, even more preferably 0.5, particularly preferably 0.4, and most preferably 0.3. When the dynamic friction coefficient between the seal layers is 1.5 or less, the opening property after bag making is good and loss during processing is likely to be reduced. The lower limit of the dynamic friction coefficient between the seal layers of the sealant film of the present invention is preferably 0.05, more preferably 0.08, and more preferably 0.1. When it is 0.05 or more, heat sealing during bag making is easy to perform and loss during processing is likely to be reduced. The upper limit of the dynamic friction coefficient between the sealing layer and the opposite surface of the film in the sealant film of the present invention is preferably 2.0, more preferably 1.5, even more preferably 1.2, still more preferably 1.0, particularly preferably 0.7, and most preferably 0.5. When the dynamic friction coefficient between the sealing layer and the opposite surface of the film is 2.0 or less, the film is less likely to wrinkle during winding, and loss during processing is likely to be reduced. The lower limit of the dynamic friction coefficient between the sealing layer of the sealant film of the present invention and the opposite surface of the film is preferably 0.05, more preferably 0.08, and even more preferably 0.1. If it is 0.05 or more, the film does not slip too much during winding, and is less likely to slip during winding. The measurement is carried out according to the method described in the Examples.

[0082] (Static friction coefficient) The upper limit of the static friction coefficient between the sealing layers of the sealant film of the present invention is preferably 1.5, more preferably 1.0, even more preferably 0.7, still more preferably 0.5, particularly preferably 0.4, and most preferably 0.3. When the dynamic friction coefficient between the sealing layers is 1.5 or less, the opening property after bag making is good, and loss during processing is likely to be reduced. The lower limit of the static friction coefficient between the sealing layers of the sealant film of the present invention is preferably 0.05, more preferably 0.08, and even more preferably 0.1. If it is 0.05 or more, heat sealing during bag making is easy to perform, and loss during processing is likely to be reduced. The measurement is carried out according to the method described in the Examples.

[0083] (Blocking value) The upper limit of the blocking value of the lubricity between the surfaces of the seal layer of the sealant film of the present invention is preferably 100 mN / 70 mm, more preferably 90 mN / 70 mm, even more preferably 80 mN / 70 mm, particularly preferably 70 mN / 70 mm, and most preferably 60 mN / 20 mm. If the blocking strength of the lubricity between the surfaces of the seal layer is 100 mN / 70 mm or less, the film can be smoothly unwound from the film roll for processing. The lower limit of the blocking strength of the surface-to-surface lubrication of the sealing layer of the sealant film of the present invention is preferably 0 mN / 70 mm, but even 15 mN / 70 mm is practically satisfactory. The measurement is carried out according to the method described in the Examples.

[0084] (150℃ easy peel strength) The 150° C. easy peel strength of the sealant film of the present invention is preferably 25 mN / 15 mm or less, more preferably 20 mN / 15 mm or less, and further preferably 15 mN / 10 mm or less. The measurement is carried out according to the method described in the Examples.

[0085] (190℃ easy peel strength) The 190° C. easy peel strength of the sealant film of the present invention is preferably 30 mN / 15 mm or less, more preferably 25 mN / 15 mm or less, and further preferably 20 mN / 15 mm or less. The measurement is carried out according to the method described in the Examples.

[0086] (200℃ easy peel strength) The 200° C. easy peel strength of the sealant film of the present invention is preferably 35 mN / 15 mm or less, more preferably 30 mN / 15 mm or less, and further preferably 25 mN / 20 mm or less. The measurement is carried out according to the method described in the Examples.

[0087] (150℃ peel strength) The 150° C. peel strength of the sealant film of the present invention is preferably 0.5 N / 15 mm or more, more preferably 0.7 N / 15 mm or more, and further preferably 0.9 N / 15 mm or more. The measurement is carried out according to the method described in the Examples.

[0088] (190℃ peel strength) The 190° C. peel strength of the sealant film of the present invention is preferably 1 N / 15 mm or more, more preferably 1.5 N / 15 mm or more, and even more preferably 1.8 N / 15 mm or more. The measurement is carried out according to the method described in the Examples.

[0089] (200℃ peel strength) The 200° C. peel strength of the sealant film of the present invention is preferably 1 N / 15 mm or more, more preferably 1.5 N / 15 mm or more, and even more preferably 1.8 N / 15 mm or more. The measurement is carried out according to the method described in the Examples.

[0090] (Laminate) The sealant film of the present invention has a laminate structure in which at least one other base film is further laminated, and is generally used as a packaging film or packaging sheet. The base film is not particularly limited, and may be appropriately selected and used depending on the intended use of the laminate, such as polyolefin films such as polyethylene and polypropylene, styrene resin films, polyester films such as polyethylene terephthalate and polybutylene terephthalate, polyamide films such as nylon 6 and nylon 6,6, or stretched films thereof, laminated films of polyolefin films and resin films having gas barrier properties such as polyamide films or ethylene-vinyl alcohol copolymer films, metal foils such as aluminum, or vapor-deposited films or papers on which aluminum, silica, etc. are vapor-deposited. The base film may be used not only as one type, but also as a combination of two or more types laminated together.

[0091] The substrate film adjacent to the sealant layer preferably does not contain the silylated polyolefin, and the substrate film adjacent to the sealant layer is preferably a polyolefin film.

[0092] The method for laminating the sealant film on the base film may include a method of dry laminating the base film (Y) and the sealant film, an extrusion lamination method in which only the sealant layer resin is extruded and laminated on the base film, etc. Among these, dry lamination is preferred from the viewpoint of productivity.

[0093] In order to bond the sealant film of the present invention to another base film more firmly, the film may have a structure of sealant film / adhesive layer / another base film. When an anchor coating agent such as a urethane-based or isocyanate-based adhesive is used as the adhesive layer, or a modified polyolefin such as an unsaturated carboxylic acid-grafted polyolefin is used as the adhesive resin, adjacent layers can be firmly bonded.

[0094] There is no particular limit to the thickness of the laminate, but when the laminate is used as a film for a lid or the like, it is preferably 10 to 200 μm, and when it is used as a sheet for cups or trays, it is preferably 200 to 1000 μm.

[0095] (packaging) A container can be manufactured by placing the sealant films of the laminate facing each other, or placing the sealant film layer of the laminate facing another base film, and then heat-sealing at least a part of the periphery from the outer surface side to form a desired container shape. A sealed bag-like container can also be manufactured by heat-sealing the entire periphery. If the molding process of this bag-like container is combined with a filling process of the contents, that is, the bottom and sides of the bag-like container are heat-sealed, the contents are filled, and then the top is heat-sealed, a package can be manufactured. Therefore, this laminate can be used in an automatic packaging device for solid, powder, or liquid materials such as snacks.

[0096] In addition, a container with the contents packaged therein can also be obtained by filling a container formed into a cup shape by vacuum forming or pressure forming, a container obtained by injection molding or blow molding, or a container formed from a paper base material with the contents, and then covering it with the laminate of the present invention as a lid material and heat sealing it. EXAMPLES

[0097] Hereinafter, the embodiment of the present invention will be described in detail with reference to examples and comparative examples, but the present invention is not limited to the following examples. The measured values ​​of the items in the detailed description of the present invention and in the examples and comparative examples were measured by the following methods.

[0098] (Characteristics of raw materials) The density, melt flow rate (MFR) and melting point of the polyolefin resin and silylated polyolefin used in the preparation of the sealant film, as well as the weight average particle size and content ratio of particles made of inorganic oxide or synthetic resin, were measured by the following methods. These values ​​may be obtained by checking the boundaries of the relevant layers with an electron microscope when the sealant film is a single layer, or by scraping off only the relevant layers when the film is a multilayer, dissolving only the desired raw material in a solvent that is insoluble in the film, filtering the solution, and then measuring the residue after removing the solvent. When scraping off only the relevant layers from a multilayer film, this can be done relatively easily by laminating the sealant film onto a polyethylene terephthalate (PET) film or the like and then scraping off the layer with a razor or the like.

[0099] (Density:kg / cm 3 ) The measurement was performed by the density gradient tube method according to JIS-K7112.

[0100] (Melt flow rate (MFR): g / 10 min) The measurements were performed in accordance with JIS-K7210 at a temperature of 190°C for polyethylene resins and 230°C for polypropylene resins.

[0101] (Melting point: ℃) Using a differential scanning calorimeter (DSC) manufactured by SII, measurements were performed with a sample weight of 10 mg and a heating rate of 10° C. / min. The melting endothermic peak temperature detected here was taken as the melting point.

[0102] (Content of inorganic oxide or synthetic resin particles in the film: wt%) The content of the particles made of inorganic oxide or synthetic resin in the film was calculated from the amount added in the raw material resin composition before processing. Even after forming a film, it is possible to separate and measure the silica particles by dissolving the film in decane as a solvent at a temperature at which it completely dissolves, and then filtering the residue through a filter with a filtration accuracy of 2 μm. (Weight average particle size of particles made of inorganic oxide or synthetic resin: μm) Particles made of inorganic oxides or synthetic resins can be calculated as the particle size that corresponds to a cumulative 50% by mass of the smallest particle size on a particle size distribution curve measured using, for example, a laser diffraction / scattering particle size distribution analyzer "MT3200II" manufactured by Nikkiso Co., Ltd.

[0103] The ease of precipitation of compounds from the resin composition constituting the sealing layer of the obtained sealant film was measured by the following method. (Ease of precipitation of compounds from the resin composition constituting the seal layer) The resin composition used for the sealing layer of Comparative Example 1 was extruded as molten resin at 230°C from multiple 4 mm diameter nozzles arranged in the width direction of the die of the extruder, and the degree of compound accumulation (degree of dirt) around the nozzles one hour after the start of extrusion was visually observed, and the results were classified as ○ or × using the criterion (○) as follows. ○: No accumulation of compounds around the nozzle was observed. ×: Deposition of compounds around the nozzle is clearly observed.

[0104] (Characteristics of sealant film) The properties of the resulting sealant films were measured by the following methods.

[0105] (Ratio of silicon atoms (Si) and carbon atoms (C) on the surface of the seal layer) Before measuring the surface of the sealant film, the surface of the seal layer was wiped with ethanol. The surface of the seal layer was excited using an X-ray electron spectroscopy (ESCA) measuring device (K-Alpha manufactured by Thermo Fisher Scientific) with excitation X-rays: monochromatic ALKα rays, X-ray output: 12 kV, 6 mA, photoelectron escape angle: 90°, spot size: 400 μmφ, pass energy: 50 eV (narrow scan), step: 0.1 eV (narrow scan), and the surface composition ratio of the detected elements was calculated. The surface composition ratio of the elements obtained is for a region having a depth of about several nm to 10 nm from the film surface.

[0106] (Ratio of silicon atoms (Si) and carbon atoms (C) contained in the sealing layer (S i / C)(Average Si concentration)) 1) After roughly understanding the layer structure by cross-sectional observation in advance, only the resin composition that constitutes the seal layer is scraped off with a feather blade. The scraped off material is completely dissolved at 135°C in a mixed solvent of o-dichlorobenzene / deuterated benzene = 80 / 20 volume ratio. The sample concentration is about 25-30mg / 0.7mL. One-dimensional S i For the NMR measurements, approximately 1 wt% of acetylacetonate chromium (III) was added to the measurement solution. The following measurements were carried out on this sample to identify the chemical formula, molecular weight, and content of the silylated polyolefin resin contained in the resin composition constituting the sealing layer. 2) First of all, 1D NMR 1 H-NMR spectrum, 13 C-NMR spectrum, 13 C-DEPT spectrum, and 29 S i Using the -NMR spectrum, the bonding of the H, C, and Si elements was investigated while referring to the Aldrich standard spectrum and standard samples, and the general structure of the compound was identified. The measurement conditions are as follows. Equipment: Fourier transform nuclear magnetic resonance spectrometer (Bruker Japan, AVANCE NEO 600) Resonance frequency::1 H-NMR: 600.13MHz, 13 C-NMR: 150.92MHz, 29 S i -NMR: 119.22MHz Measurement temperature:: 1 H-NMR: 110 or 115° C. 13 C-NMR: 110 or 115° C. 13 C-DEPT: 110 or 115°C, 29 Si-NMR: 110℃ Pulse Repetition Time: 1 H-NMR: 3.75 seconds, 13 C-NMR: 2.8~2.9 seconds, 13 C-DEPT: 3.5 seconds, 29 S i -NMR:7.0 seconds Detection pulse angle: 1 H-NMR: 30°, 13 C-NMR: 30°, 29 S i -NMR:90° 1 How to H-decouple: 13 C-NMR: fully decoupled, 29 S i -NMR: Inverse gate decoupled (FID acquisition time 0.7 seconds) Number of times: :1 H-NMR: 16 times, 13 C-NMR: about 300 to 1200 times, 13 C-DEPT: Approximately 100 to 1100 times, 29 S i -NMR: Approximately 4000 times 3) In addition, 2D NMR such as COSY and TOCSY, 13 C-HSQC, HMBC, 29 S i -HMBC is used to 1 The correlation peak between H, and the neighboring H, and the neighboring H, are connected. 1 Correlation peak between H and directly bonded 1 H, 13 C correlation peak, heteronuclear species separated by two or three bonds ( 1 H, 13C) correlation peaks, heteronuclear species separated by two or three bonds ( 1 H, 29 Si) correlation peaks were examined to identify in more detail the structure connections found by 1D NMR. 4) The ratio of silicon atoms per carbon atom in the resin composition constituting the seal layer of the sealant film (S i / C) (average Si concentration) can be calculated from the molecular formula and molecular weight of the silylated polyolefin resin contained in the resin composition, and the content ratio in the resin composition constituting the sealing layer. As a specific example, the calculation method is given below when the resin composition constituting the seal layer is a mixture of a polymer consisting only of ethylene-derived structural units containing a vinyl group at the main chain end, a silylated polyolefin resin made from dimethylsiloxane as a raw material compound, and a polyethylene resin. The dimethylsiloxane concentration in the silylated polyolefin was calculated from the molecular formula of the silylated polyolefin resin. If this resin concentration was assumed to be 26% by weight, the average polydimethylsiloxane concentration in a composition obtained by adding 10 parts by weight of the silylated polyolefin to 90 parts by weight of polypropylene resin would be 2.6% by weight. The molecular formula for one unit of dimethylsiloxane is C2H6S i The molecular formula per polyolefin unit of the silylated polyolefin resin is C2H4 (unit molecular weight 28.05), and the molecular formula per propylene unit of the polypropylene resin is C3H6 (unit molecular weight 42.08). The amount of dimethylsiloxane per 1 kg of resin composition is (1000 x 2.6 / 100) / 74.15 = 0.35 mol, the amount of polyolefin in the silylated polyolefin resin is (1000 x (10-2.6) / 100) / 28.05 = 2.6 mol, and the amount of polypropylene resin is (1000 x 90 / 100) / 42.08 = 21.4 mol. Therefore, per 1 kg of resin composition, S i (silicon) is 0.35 mol, and C (carbon) is 0.35×2+2.6×2+21.4×2=48.7 mol. The silicon atom abundance ratio (S i / C) is calculated as 0.35 / 48.7 = 0.007.

[0107] (Arithmetic mean roughness Ra:μm) The arithmetic mean roughness Ra of an arbitrary 1 mm x 0.2 mm area on the surface of the sealing layer of a 3 cm x 3 cm square sealant film was measured using a contact surface roughness tester (Kosaka Laboratory, Model ET4000A) in accordance with JIS B0601-2001. Measurements were taken at three locations, and the average value was taken as the arithmetic mean roughness Ra.

[0108] (Maximum protrusion height Rz:μm) The maximum peak height Rz of any 1 mm x 0.2 mm part on the surface of the sealing layer of a 3 cm x 3 cm square sealant film was measured using a contact surface roughness tester (Kosaka Laboratory, Model ET4000A) in accordance with JIS B0601-2001. Measurements were taken at three locations, and the average value was taken as the maximum peak height Rz.

[0109] (Young's modulus, tensile breaking strength, tensile breaking elongation) The Young's modulus of the obtained sealant film in the longitudinal direction and width direction of the film was measured at 23° C. in accordance with JIS K7127. A sample was cut out from the film to a size of 15 mm x 200 mm, and set in a tensile tester (Instron 5965 dual column tabletop tester manufactured by Instron Japan Co., Ltd.) with a chuck width of 100 mm. A tensile test was performed at a tensile speed of 200 mm / min. From the obtained strain-stress curve, Young's modulus was calculated from the slope of the linear portion in the initial stage of elongation. The tensile breaking strength and tensile breaking elongation were respectively the strength and elongation at the time when the sample broke.

[0110] (Hayes) Only the obtained sealant film was measured for haze using a direct reading haze meter manufactured by Toyo Seiki Seisakusho Co., Ltd. in accordance with JIS-K-7105. Haze (%) = [Td (diffuse transmittance %) / Tt (total light transmittance %)] x 100

[0111] (liquid repellency) The liquid repellency of the obtained sealant film was evaluated as follows. (1) The sealant film was cut into a size of 10 cm in the longitudinal direction and 5 cm in the width direction. Double-sided tape (Nichiban Co., Ltd., NW-5, 5 mm width) was attached to the surface of the laminate layer at the end of one longitudinal side and the end of the adjacent width direction. The film was folded in the center of the width direction so that the sealing surface was on the outside, and the double-sided tape was attached to the other laminate layer surface to create a cylindrical strip of 10 cm x 2.5 cm. (2) The weight of the cylindrical strip prepared in (1) was measured. (3-1) The following evaluation liquids were placed in a 100 ml death cup so that each liquid was about 70% of the volume. A weighed cylindrical strip was immersed in the evaluation liquid for 1 second so that it was immersed up to a position 5.6 cm from the bottom. When immersing, inserting a metal ruler or similar support into the opening of the cylindrical strip during immersion makes it easier to handle and prevents the opening of the bag from being immersed in the evaluation liquid by mistake. Evaluation liquids: edible oil (product name: Nissin salad oil, manufactured by Nisshin Oillio Group, Ltd.), tonkatsu sauce (product name: thick sauce, manufactured by Kagome Co., Ltd.), soy sauce (product name: Koikuchi soy sauce (honjozo), manufactured by Kikkoman Foods Co., Ltd.). (3-2) With the evaluation liquid still attached to the cylindrical strip, the cylindrical strip was hung for 10 seconds with its length direction vertical, and then it was hung for 50 seconds with its length direction tilted at 45° to the horizontal while keeping its width direction horizontal. (4) The weight of the cylindrical strip with the evaluation liquid attached immediately after (3-2) was weighed, and the amount of remaining liquid was calculated from the difference between the weight and (2). The surface area of ​​the cylindrical strip from the bottom to the position 5.6 cm from the bottom was 28 cm 2 It is. Two or more of the three evaluation liquids were 0.08 / 8cm 2 If it exceeds 0.08 / 8cm, it is considered inferior. 2 The following cases are good, three types are 0.08 / 8cm 2 The following cases were rated as excellent ◎.

[0112] (Observation of the dispersion state of silylated polyolefin) The surface of the seal layer of the obtained sealant film was observed using a scanning electron microscope and irradiated with energy dispersive X-rays to perform elemental qualitative analysis and mapping of the surface. The cross section was also observed using a transmission electron microscope. The observation method is described in detail below.

[0113] (Energy dispersive X-ray (EDX) elemental qualitative analysis) A sample (1 cm x 1 cm) was cut out of the obtained sealant film, placed on a sample stage with carbon tape attached, coated with approximately 2 nm of platinum-palladium using a magnetron sputtering device to ensure conductivity, and observed in high vacuum mode. The measurements were performed using a Hitachi S-3400N scanning electron microscope and a Bruker XFlash5010 energy dispersive X-ray detector, irradiating X-rays at an accelerating voltage of 8 kV. A qualitative analysis of the elements was carried out from the X-ray spectrum of the entire observation field of the sealant film sample, and of the elements observed, carbon (C) was mapped in red and silicon (Si) in green.

[0114] (Transmission electron microscope (TEM) observation) Both sides of the resulting sealant film (1 cm x 1 cm) were subjected to osmium deposition, and after treatment to prevent peeling from the epoxy resin, it was embedded in the epoxy resin. The embedded samples were cut perpendicular to the film surface in a frozen state using a cryomicrotome set at -130°C to obtain ultrathin sections. The cross section was stained in ruthenium tetroxide vapor for 30 minutes, then carbon deposition was performed, and the cross section was observed and photographed using a JEOL JEM2100 transmission electron microscope at an accelerating voltage of 200 kV.

[0115] (Kinematic friction coefficient) The dynamic friction coefficient was measured for each film surface of the polyethylene resin sealant film in accordance with JIS-K-7125 except for the conditions below. Environmental conditions: 23°C, 50% RH. Measurements were taken after regulating humidity for at least 2 hours. Measuring device: Toyo Baldwin TENSILON STM-T-50BP Measurement conditions: Size of fixed test piece: 297mm (longitudinal) x 105mm (lateral) Size of moving test piece: 70mm (longitudinal) x 50mm (lateral) Weight of load: 0.5kg Crosshead speed: 20mm / min Travel distance: 100mm or more Calculation method: Calculated from the average test force between 10mm and 50mm stroke and the mass of the load weight using the following formula. Friction coefficient = average test force over a stroke of 10mm to 40mm / mass of the load

[0116] (Static friction coefficient) The static friction coefficient was measured for each film surface of the polyethylene resin sealant film in accordance with JIS-P-8147, except for the conditions below. Environmental conditions: 23°C, 50% RH. Measurements were taken after regulating humidity for at least 2 hours. Measuring device: Friction measuring device AN manufactured by Toyo Seiki Co., Ltd. Measurement conditions: Size of test piece: 200mm (longitudinal direction) x 100mm (lateral direction) Size of the load: 100mm (longitudinal) x 60mm (lateral) Weight of load: 1.0kg Tilt speed: 1.5° / sec Measurement method: One test piece was fixed to an inclined plate, and the weight with the other test piece attached was gently placed on it. The plate was then tilted at a constant speed, and the tangent (tanθ) of the angle at which the test piece with the weight attached began to slide was calculated, and this was taken as the static friction coefficient. The test was performed three times, and the average value was calculated.

[0117] (Blocking value) ASTM D2011-2006: Testing was performed on the sealant layer surfaces of the sealant film under the following conditions. The blocking value was measured in accordance with D1893-67. The samples (10 cm wide, 15 cm long) with the measurement surfaces overlapping each other were placed in a heat press (Tester Sangyo Co., Ltd., model: SA-303) so that the edge of a 7 cm x 7 cm aluminum plate (2 mm thick) was aligned at the center of the sample width (10 cm) and 1 cm inside the length direction (15 cm). The temperature was 50°C and the pressure was 440 kgf / cm. 2 The mixture was subjected to pressure treatment for 15 minutes. The sample blocked by this pressure treatment and a bar (diameter 6 mm, material: aluminum) were attached to an autograph (Shimadzu Corporation, model: UA-3122) and the force at which the bar peeled off the blocked portion at a speed of 100 m / min was measured. In this case, it is assumed that the bar and the peeled surface are horizontal. The same sample was measured four times and the average value was displayed.

[0118] (Easy peeling) The easy peel property was measured by the easy peel strength when sealed at 190°C. A strength of 20 mN / 15 mm or less was rated as excellent (◎), 30 mN / 15 mm or less was rated as good (◯), and anything over 30 mN / 15 mm was rated as poor (×).

[0119] (Easy peel strength: mN / 15mm) A dry lamination adhesive (TM569, CAT-10L) made by Toyo-Morton was applied to the corona surface of a nylon film (Toyobo biaxially oriented nylon film: N1100, 15 μm) at a solid content of 3 g / m 2 The solvent was removed by volatilization in an oven at 80° C., and then the corona surface of the sealant film and the adhesive-coated surface of the nylon film were nipped and laminated on a temperature-controlled roll at 60° C. The laminated film was aged at 40° C. for 2 days, and the laminated film was sampled. The sealant surface of the collected laminate film was overlapped with 300 μm of an unstretched CPP sheet (WF577PG x 100%), and heat sealed with a seal width of 15 mm, a seal pressure of 0.2 MPa, a seal time of 1.0 second, and seal temperatures of 150, 190°C, and 200°C. The laminate obtained by heat sealing was cut in parallel to the longitudinal direction to obtain a test piece having a width of 15 mm. The test pieces were set in an autograph (Shimadzu Corporation, Model: UA-3122) and the seal surface was peeled off at a speed of 200 mm / min to measure the maximum peel strength. Three test pieces were measured at each sealing temperature, and the average value was taken as the easy peel strength at each sealing temperature.

[0120] (Peel strength: mN / 15mm) A dry lamination adhesive (TM569, CAT-10L) made by Toyo-Morton was applied to the corona surface of a nylon film (Toyobo biaxially oriented nylon film: N1100, 15 μm) at a solid content of 3 g / m 2 The solvent was removed by volatilization in an oven at 80° C., and then the corona surface of the sealant film and the adhesive-coated surface of the nylon film were nipped and laminated on a temperature-controlled roll at 60° C. The laminated film was aged at 40° C. for 2 days, and the laminated film was sampled. The collected laminated films were heat sealed with their longitudinal directions aligned and the sealant films facing each other, with a sealing width of 15 mm, sealing pressures of 0.2, 0.4, and 0.6 MPa, sealing time of 1.0 second, and sealing temperatures of 150, 190°C, and 200°C. The laminate obtained by heat sealing was cut in parallel to the longitudinal direction to obtain a test piece having a width of 15 mm. The test pieces were set in an autograph (Shimadzu Corporation, Model: UA-3122) and the seal surface was peeled off at a speed of 200 mm / min to measure the maximum peel strength. Three test pieces were measured at each sealing temperature, and the average value was taken as the peel strength at each sealing temperature.

[0121] The following raw materials were used in the examples and comparative examples. (Polypropylene resin) (1) WF577PG (ethylene copolymer polypropylene, manufactured by Sumitomo Chemical Co., Ltd., MFR 3.2 g / 10 min, melting point 142°C) (2) EP3721 (propylene-ethylene block copolymer, manufactured by Sumitomo Chemical Co., Ltd., MFR 2.5 g / 10 min, melting point 143°C) (2) (Polyethylene resin) (1) F222 (low density polyethylene, manufactured by Ube Maruzen Polyethylene Co., Ltd., density 922 kg / m 3 , MFR2.0g / 10min, melting point 110℃) (2) FV407 (metallocene-based linear low-density polyethylene, manufactured by Sumitomo Chemical Co., Ltd., density 930 kg / m 3 , MFR3.2g / 10min, melting point 124℃) (3) A-4070S (ethylene-α-olefin copolymer, manufactured by Mitsui Chemicals, Inc., density 870 kg / m 3 , MFR3.6g / 10min, melting point 55℃) (4) A-1085S (ethylene-alpha-olefin copolymer, manufactured by Mitsui Chemicals, Inc., density 885 kg / m 3 , MFR1.2g / 10min, melting point 66℃) (5) RS1405 (mixture of ethylene-alpha-olefin copolymers, manufactured by Mitsui Chemicals, Inc.) (6) P0480 (ethylene-alpha-olefin copolymer, manufactured by Mitsui Chemicals, Inc., MFR 1.8g / 10min)

[0122] (Silylated polyolefin resin) (1) Exfora PP2000 (manufactured by Mitsui Fine Chemicals, Inc., contains 30% by weight of silylated polyprefin (olefin-silicone copolymer), 70% by weight of polypropylene, and has a density of 917 kg / m 3 , MFR 20g / 10min, melting point 125℃ and 160℃) (2) Exfora PE3027 (manufactured by Mitsui Chemicals Fine Co., Ltd., contains 30% by weight of silylated polyprefin (olefin-silicone copolymer), 70% by weight of low-density polyethylene, density 932kg / m 3 , MFR 30g / 10min, melting points 114℃ and 122℃) (3) EXFOLA LL1513 (manufactured by Mitsui Chemicals Fine Co., Ltd., contains 30% by weight of silylated polyprefin (olefin-silicone copolymer), 70% by weight of metallocene-based linear low-density polyethylene, and has a density of 921 kg / m 3 , MFR15g / 10min, melting points 102℃ and 121℃)

[0123] (Particles made of inorganic oxides) Mixed pellets (MB) of (1) / (2) / (3)=90 / 6 / 4 (weight%) (1) WF577PG (ethylene copolymer polypropylene) (2) KMP-130-10 (spherical silica particles, manufactured by Shin-Etsu Silicones, weight average particle size 10 μm) (3) KMP-130-4 (spherical silica particles, manufactured by Shin-Etsu Silicones, weight average particle size 10 μm)

[0124] (Organic lubricants) (1) MS07 (containing 5% by weight of erucic acid amide, manufactured by Sumitomo Chemical Co., Ltd.)

[0125] (Examples 1 to 12) Polypropylene resin, polyethylene resin, silylated polyolefin, spherical silica, diatomaceous earth, ethylene bisoleamide, and erucamide were mixed and melted in a twin-screw extruder so as to obtain the content ratio (weight %) shown in Table 1 to form a sealing layer.

[0126] Further, polypropylene resin and erucic acid amide were mixed and melted in a twin-screw extruder so as to have the content ratio (wt %) shown in Table 1 to form an intermediate layer.

[0127] Furthermore, as shown in Table 1, polypropylene resin was melted in a twin-screw extruder to form a laminate layer.

[0128] Using a multilayer film molding device, the molten resin composition for the sealant layer, the resin composition for the intermediate layer, and the resin composition for the laminate layer were laminated together, and a single multilayer molten sheet was co-extruded through a T-die. The sheet was then brought into contact with a cooling roll to cool and solidify, thereby obtaining an unstretched sheet. The laminate surface of the obtained sheet was subjected to a corona discharge treatment, and then wound into a roll at a speed of 20 m / min to obtain a sealant film with a thickness of 60 μm and a wet tension of the laminate surface of 45 N / m. The detailed conditions are as follows: Sealant layer extruder diameter: 60mm Diameter of middle layer extruder: 90mm Diameter of extruder of laminate layer: 45mm Melting temperature of the raw materials for the sealant layer, intermediate layer, and laminate layer: 250℃ T-die width: 1600mm Multi-layer molten sheet take-up speed: 20m / min Cooling roll temperature: 40℃ Thickness of the sealant layer in the sealant film: 6 μm Thickness of the middle layer in the sealant film: 42μm Thickness of laminate layer in sealant film: 12μm The longitudinal direction means the direction in which the unstretched sheet was run, and the transverse direction means the direction perpendicular to the longitudinal direction. The properties of the obtained film are shown in Table 2.

[0129] The sealant films obtained in Examples 1 to 13 were excellent in liquid repellency and heat sealability. They also had excellent easy peel properties. Moreover, the resin composition used in the sealing layer had little compound precipitation and was excellent in film-forming processability. The reason for this is that the silylated polyolefin used in the sealing layer contains a dimethylsiloxane component, so that the surface energy is small and the silylated polyolefin segregates on the surface of the sealing layer. FIG. 1 shows the average Si concentration and surface Si concentration of the films described in Comparative Examples 1 and 4, and Examples 2 to 4, and 13. It is clear that the Si concentration at the surface of the sealing layer of the films described in Comparative Examples 1 and 4, and Examples 2 to 4, and 13 is up to about 46.5 times higher than the average Si concentration in the entire sealing layer, indicating that silylated polyolefin is segregated on the surface.

[0130] Figure 3 shows the analysis images of silicon mapping of the sealing layer surface of Example 2 and Comparative Example 1. Silicon (green) is present over the entire surface in Example 2, but is not seen in Comparative Example 1. Silica particles are highlighted because they are mainly composed of silicon. Fig. 4 shows TEM images of the cross section of the seal layer in Example 2 and Comparative Example 7. Since the silylated polyolefin in Example 2 is a copolymer of dimethylsiloxane and polyethylene, it is difficult for dimethylsiloxane to separate from polyethylene, and therefore, although it exhibits a microphase separation structure, it is only finely dispersed. On the other hand, Comparative Example 7 contains a silicone resin, which is thought to have undergone phase separation or precipitation. Figure 5 is a photograph of the vicinity of the die nozzle in which the seal layer raw materials of Example 2 and Comparative Example 7 were melt-kneaded in a twin-screw extruder. In Example 2, no compound deposition was observed, and it is considered that the silylated polyolefin in the seal layer does not precipitate on its surface. On the other hand, in Comparative Example 7, precipitation of the silicone resin was observed, and there are concerns about foreign matter in the film and deterioration of the working environment.

[0131] (Comparative Examples 1 to 7) A sealant film was obtained in the same manner as in Example 1, except that the compounds shown in Table 1 were used as raw materials for the resin compositions of the seal layer, laminate layer, and intermediate layer.

[0132] The sealant film obtained in Comparative Example 1 was poor in liquid repellency and easy peelability.

[0133] The sealant film obtained in Comparative Example 2 was excellent in liquid repellency but had poor easy peelability.

[0134] The sealant film obtained in Comparative Example 3 was poor in liquid repellency.

[0135] The sealant film obtained in Comparative Example 4 was excellent in liquid properties but had poor easy peel properties.

[0136] The sealant film obtained in Comparative Example 5 was excellent in liquid repellency but had poor easy peelability.

[0137] The sealant film obtained in Comparative Example 6 was excellent in liquid repellency but had poor easy peelability. Although the film had excellent liquid repellency and low blocking value and friction coefficient, the compound was prone to precipitate from the sealing layer, making it inferior as a sealant film.

[0138] The sealant film obtained in Comparative Example 7 was excellent in liquid properties but had poor easy peel properties. Although the film had excellent liquid repellency and low blocking value and friction coefficient, the compound was prone to precipitate from the sealing layer, making it inferior as a sealant film.

[0139] [Table 1]

[0140] [Table 2] [Industrial Applicability]

[0141] INDUSTRIAL APPLICABILITY The sealant film of the present invention can provide a sealant film and a laminate thereof that are easy to remove even when the contents are pasty, viscous, or other viscous contents, and have good heat sealability and excellent easy peel properties, making a great contribution to the industry.

Claims

1. A film for sealant comprising a seal layer made of a resin composition containing the following (a), (b), and (c), and satisfying the following (1), (2), (3), (7), and (8). (a) Polypropylene resin (b) Polyethylene resin (c) Silylated polyethylene resin (1) The contents of (a), (b) and (c) are 30 to 70% by weight, 10 to 40% by weight and 3 to 30% by weight, respectively, based on the total weight of the resin composition. (2) Silylated polyethylene resin is represented by the following formula: CH 3 -(CH 2 ) n-2 -CH 2 -S i (CH 3 ) 2 O-(-S i (CH 3 ) 2 -O-) d -S i (CH 3 ) 2 -CH 2 -(CH 2 ) n-2 -CH 3 (In the formula, d is an integer of 1 or more, and n is an integer of 100 or more.) (3) The polyethylene resin is a high-pressure low-density polyethylene. (7) The resin composition contains particles made of an inorganic oxide or a synthetic resin. (8) The blocking value of the surface of the sealing layer is 200 mN / 70 mm or less.

2. A film for sealant comprising a seal layer made of a resin composition containing the following (a), (b), and (c), and satisfying the following (1), (2), (3), (7), and (8). (a) Polypropylene resin (b) Polyethylene resin (c) Silylated polyethylene resin (1) The contents of (a), (b) and (c) are 30 to 70% by weight, 10 to 40% by weight and 3 to 30% by weight, respectively, based on the total weight of the resin composition. (2) Silylated polyethylene resin is represented by the following formula: CH 3 -(CH 2 ) n-2 -CH 2 -S i (CH 3 ) 2 O-(-S i (CH 3 ) 2 -O-) d -S i (CH 3 ) 2 -CH 2 -(CH 2 ) n-2 -CH 3 (In the formula, d is an integer of 1 or more, and n is an integer of 100 or more.) (3) The polyethylene resin is a linear low-density polyethylene. (7) The resin composition contains particles made of an inorganic oxide or a synthetic resin. (8) The blocking value of the surface of the sealing layer is 200 mN / 70 mm or less.

3. A film for sealant comprising a seal layer made of a resin composition containing the following (a), (b), and (c), and satisfying the following (4), (5), (6), (7), and (8). (a) Polypropylene resin (b) Polyethylene resin (c) Silylated polyethylene resin (4) The contents of (a), (b) and (c) are 30 to 85% by weight, 10 to 40% by weight and 3 to 30% by weight, respectively, based on the total weight of the resin composition. (5) Silylated polyethylene resin is represented by the following formula: CH 3 -(CH 2 ) n-2 -CH 2 -S i (CH 3 ) 2 O-(-Si(CH 3 ) 2 -O-) d -Si(CH3) 2 -CH 2 -(CH 2 ) n-2 -CH 3 (In the formula, d is an integer of 1 or more, and n is an integer of 100 or more.) (6) The polyethylene resin is an elastomer made of a copolymer of an ethylene monomer and an α-olefin. (7) The resin composition contains particles made of an inorganic oxide or a synthetic resin. (8) The blocking value of the surface of the sealing layer is 200 mN / 70 mm or less.

4. The sealant film according to any one of claims 1 to 3, wherein the resin composition contains a fatty acid amide.

5. A laminate comprising the sealant film according to any one of claims 1 to 3 and a base film.

6. A container comprising the laminate according to claim 5.

Citation Information

Patent Citations

  • Production of fruit liquor

    JP1978094096A

  • Transfer device of direct memory access

    JP1984090131A

  • Packaging material having water-repellence and mold release property to contents

    JP1996337267A

  • Filling package for viscous matter, laminated film for filling package for viscous matter, and manufacture of filling package for viscous matter

    JP2000355362A

  • Shrink package filled with viscous object and laminated film for shrink packaging for filling viscous object

    JP2001048229A